Paradigma Etika yang Mendasari Moral dan Karakter Siswa Sekolah Dasar di Abad 21 - Husnah, Farah Miftahul; Hanan, Nabilla; Hasanah, Isnaini Mau’idzoh; Hartono, Rafli Rizky Tha-ariq (Journal of Classroom Action Research, 2023)
This journal is motivated by the field of education which is a sector of change and paradigm shift that is carried out for the sake of creating a golden generation with good character and morals in 2045. In an era of social change, technology, and the complexity of moral issues, the ethical paradigm that underlies morals and the character of elementary school students in the 21st century is very important. This article aims to analyze relevant ethical paradigms in the 21st century context and the importance of their application in the moral and character development of elementary school students. The ethical paradigms described in this article cover the development of moral awareness, character education, digital ethics, multiculturalism and tolerance, social skills and empathy, and environmental education. This article also discusses the important role of schools, families and communities in implementing this ethical paradigm in education. It is hoped that this article can provide a better understanding of the importance of the ethical paradigm that underlies the morals and character of elementary school students in the 21st century